2008
DOI: 10.1021/ic8007365
|View full text |Cite
|
Sign up to set email alerts
|

Halide Ligands—More Than Just σ-Donors? A Structural and Spectroscopic Study of Homologous Organonickel Complexes

Abstract: The isoleptic organonickel complexes [(bpy)Ni(Mes)X] (bpy ) 2,2'-bipyridine; Mes ) 2,4,6-trimethylphenyl; X ) F,Cl, Br, or I, and for comparison X ) OMe and SCN) have been investigated by multiple spectroscopic means.Their structures have been determined in part by single-crystal X-ray diffraction, the full series by extended X-ray absorption fine structure. The long-wavelength charge transfer absorptions (mainly metal-to-ligand charge transfer)obtain contributions from the mesityl coligand but are almost inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 67 publications
10
40
0
Order By: Relevance
“…[14,16] In nitriles, DMSO and alcohols the complexes undergo the same decomposition reaction as reported for a number of monomolecular diimine complexes [(N ∧ N)NiMesX] (N ∧ N = various diimine ligands, X = halogenido). [14][15][16] This will be important for the further measurements in THF or DMF solutions (see below). 1 H NMR spectra revealed that the binuclear complex was obtained as 1.45 trans/1 cis mixtures of the two stereoisomers depicted in Scheme 1.…”
Section: Synthesis and General Propertiessupporting
confidence: 52%
See 2 more Smart Citations
“…[14,16] In nitriles, DMSO and alcohols the complexes undergo the same decomposition reaction as reported for a number of monomolecular diimine complexes [(N ∧ N)NiMesX] (N ∧ N = various diimine ligands, X = halogenido). [14][15][16] This will be important for the further measurements in THF or DMF solutions (see below). 1 H NMR spectra revealed that the binuclear complex was obtained as 1.45 trans/1 cis mixtures of the two stereoisomers depicted in Scheme 1.…”
Section: Synthesis and General Propertiessupporting
confidence: 52%
“…Based on similar results from mononuclear derivatives, we assign them to metal-centred oxidations Ni II /Ni III for the two nickel atoms. [16,17] From the wave of the binuclear complex it is not discernible if both nickel atoms are oxidised at the same potential (no electronic coupling), or if a mixed-valent state occurs (coupling of the metal centres).…”
Section: Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…[16] However, the pre-edge of 1 NO3 having an intensity of ~0.3 units is similar to the well resolved preedge of a previously reported square planar Ni II complex, [(bpy)Ni(Mes)Cl], having a Ni-C aryl bond of 1.94 Å. [17] This can be explained by the highly covalent nature of the Ni-C bond, which facilitates p-d mixing through a configuration interaction model, as previously described. [18] Furthermore, the strength of the Ni-C aryl interaction in 1 NO3 is further highlighted by the lower energy of the features due to 1sà4p + shake-down contributions which occur ~2 eV lower in energy than in either the previously reported [(bpy)Ni(Mes)Cl] complex having a Ni-C aryl bond of 1.94 Å or the [Ni(cyclam)](ClO 4 ) 2 analogue having no Ni-C bond.…”
Section: N1 Ni1supporting
confidence: 83%
“…The role of the iodide may be to (1) help facilitate reduction of the nickel catalyst by acting as a bridging ligand with zinc, 56,18 (2) promote formation of more reactive nickelate complexes, 57,18 (3) generate a small amount of the more reactive alkyl iodide in situ, 58 and/or (4) facilitate ligand exchange reactions. 59 The addition of more sodium iodide (>25 mol %) was not helpful except in the synthesis of 3ac , which was slow to react and for which S N 2 reactions are a challenge. 60 The effect of sodium iodide on reactions to form 3b – 3d are shown below (Table 4).…”
Section: Discussionmentioning
confidence: 99%